A Class of its Own: The Role of Sustainable Real Estate in a Multi-Asset Portfolio. Issue 1 (1st November 2016) - Geiger, Peter; Cajias, Marcelo; Fuerst, Franz
Abstract : In this paper, we analyze the effect of socially responsible investments within a multi-asset portfolio optimization model. We also attempt to bridge the gap in the real estate literature between sustainability principles and investment analysis. To this aim, listed real estate companies with an active sustainability agenda, identified through the MSCI ESG database, represent the sustainable real estate asset class. Applying a downside risk approach by using a conditional value at risk (CVaR) optimization technique, we establish empirically whether diversification benefits can be achieved by investing in companies with a proven track record in sustainability. Our results highlight the potential contribution of listed real estate companies with high sustainability ratings to an institutional investor's portfolio taking into account differences in investment style and risk aversion.